Preparation of PEDOT-modified double-layered hollow carbon spheres as Pt catalyst support for methanol oxidation. (8th September 2021) - Niyaz, Mariyam; Sawut, Nurbiye; Jamal, Ruxangul; Abdiryim, Tursun; Helil, Zulpikar; Liu, Haile; Xie, Shuyue; Song, Yanyan
Abstract: In this paper, Pt nanoparticles (Pt NPs) deposited hybrid carbon support is prepared by modifying double-layered hollow carbon spheres（DLHCs）with poly(3, 4-ethylenedioxythiophene) (PEDOT) and used as anode catalyst of methanol oxidation. The structure of nanocomposites is characterized by SEM, TEM, FT-IR, XRD and XPS, confirming the greatly enhanced synergistic effect between the PEDOT and DLHCs, and illustrating the uniform distribution of Pt NPs on the PEDOT/DLHCs composite surface with a small particle size ( 2.63 nm). Cyclic voltammetry, chronoamperometry and impedance spectroscopy applied to determine the electrocatalytic activity of catalysts, it is found that the synthesized PEDOT/DLHCs/Pt possesses excellent characteristics such as large electrochemically active surface area and high mass activity of 59.45 m 2 g −1 and 807 mA mg −1 in 0.5 M H2 SO4 containing 1 M methanol solution, which is almost 1.24 and 2.8 times greater than those of commercial Pt/C, and the catalyst exhibits superior stability after 500 durability cycles. The enhanced electrocatalytic behavior can be ascribed to the excellent electronic conductivity of PEDOT-modified DLHCs and the strong binding of PEDOT/DLHCs to Pt NPs, suggesting that the PEDOT/DLHCs/Pt is a promising electrocatalyst for direct methanol fuel cell. Highlights: DLHCs provides large contact platform for the combination of PEDOT and Pt NPs. 3D network structured PEDOT/DLHCs facilitates the electronic transferring. Strong interaction allows the Pt NPs uniformly anchored on PEDOT/DLHCs. The PEDOT/DLHCs/Pt exhibits high catalytic activity and durability for MOR.